Tropical cyclone activity affected by volcanically induced ITCZ shifts - Pausata, Francesco S. R.; Camargo, Suzana J. (Proceedings of the National Academy of Sciences, 2019)
Significance Volcanic eruptions can inject a large amount of aerosol particles, which interact with solar radiation and consequently can affect the climate worldwide, hence the intensity and frequency of extreme events for a few years following the eruption. However, only a handful of studies have investigated the impacts of volcanic eruptions on tropical cyclone activity. Through a set of sensitivity modeling experiments, our study demonstrates that volcanic eruptions by shifting the Intertropical convergence zone can impact tropical cyclone activity up to 4 years following the eruption. These results will prove valuable to society, allowing us to better prepare for the consequences of changes in tropical cyclone activity following large volcanic eruptions. , Volcanic eruptions can affect global climate through changes in atmospheric and ocean circulation, and therefore could impact tropical cyclone (TC) activity. Here, we use ensemble simulations performed with an Earth System Model to investigate the impact of strong volcanic eruptions occurring in the tropical Northern (NH) and Southern (SH) Hemisphere on the large-scale environmental factors that affect TCs. Such eruptions cause a strong asymmetrical hemispheric cooling, either in the NH or SH, which shifts the Intertropical Convergence Zone (ITCZ) southward or northward, respectively. The ITCZ shift and the associated surface temperature anomalies then cause changes to the genesis potential indices and TC potential intensity. The effect of the volcanic eruptions on the ITCZ and hence on TC activity lasts for at least 4 years. Finally, our analysis suggests that volcanic eruptions do not lead to an overall global reduction in TC activity but rather a redistribution following the ITCZ movement. On the other hand, the volcanically induced changes in El Niño-Southern Oscillation (ENSO) or sea-surface temperature do not seem to have a significant impact on TC activity as previously suggested.

The water cycle of the mid‐Holocene West African monsoon: The role of vegetation and dust emission changes - Messori, Gabriele; Gaetani, Marco; Zhang, Qiang; Zhang, Qiong; Pausata, Francesco S. R. (International Journal of Climatology, 2019)
During the mid‐Holocene (6 kyr BP), West Africa experienced a much stronger and geographically extensive monsoon than in the present day. Changes in orbital forcing, vegetation and dust emissions from the Sahara have been identified as key factors driving this intensification. Here, we analyse how the timing, origin and convergence of moisture fluxes contributing to the monsoonal precipitation change under a range of scenarios: orbital forcing only; orbital and vegetation forcings (Green Sahara); orbital, vegetation and dust forcings (Green Sahara‐reduced dust). We further compare our results to a range of reconstructions of mid‐Holocene precipitation from palaeoclimate archives. In our simulations, the greening of the Sahara leads to a cyclonic water vapour flux anomaly over North Africa with an anomalous westerly flow bringing large amounts of moisture into the Sahel from the Atlantic Ocean. Changes in atmospheric dust under a vegetated Sahara shift the anomalous moisture advection pattern northwards, increasing both moisture convergence and precipitation recycling over the northern Sahel and Sahara and the associated precipitation during the boreal summer. During this season, under both the Green Sahara and Green Sahara‐reduced dust scenarios, local recycling in the Saharan domain exceeds that of the Sahel. This points to local recycling as an important factor modulating vegetation‐precipitation feedbacks and the impact of Saharan dust emissions. Our results also show that temperature and evapotranspiration over the Sahara in the mid‐Holocene are close to Sahelian pre‐industrial values. This suggests that pollen‐based paleoclimate reconstructions of precipitation during the Green Sahara period are likely not biased by possible large evapotranspiration changes in the region.

Enhanced Himalayan Glacial Melting During YD and H1 Recorded in the Northern Bay of Bengal - Weldeab, Syee; Rühlemann, Carsten; Bookhagen, Bodo; Pausata, Francesco S. R.; Perez‐Lua, Fabiola M. (Geochemistry, Geophysics, Geosystems, 2019)
Abstract Ocean‐land thermal feedback mechanisms in the Indian Summer Monsoon (ISM) domain are an important but not well understood component of regional climate dynamics. Here we present a δ 18 O record analyzed in the mixed‐layer dwelling planktonic foraminifer Globigerinoides ruber ( sensu stricto ) from the northernmost Bay of Bengal (BoB). The δ 18 O time series provides a spatially integrated measure of monsoonal precipitation and Himalayan meltwater runoff into the northern BoB and reveals two brief episodes of anomalously low δ 18 O values between 16.3±0.4 and 16±0.5 and 12.6±0.4 and 12.3±0.4 thousand years before present. The timing of these events is centered at Heinrich event 1 and the Younger Dryas, well‐known phases of weak northern hemisphere monsoon systems. Numerical climate model experiments, simulating Heinrich event‐like conditions, suggest a surface warming over the monsoon‐dominated Himalaya and foreland in response to ISM weakening. Corroborating the simulation results, our analysis of published moraine exposure ages in the monsoon‐dominated Himalaya indicates enhanced glacier retreats that, considering age model uncertainties, coincide and overlap with the episodes of anomalously low δ 18 O values in the northernmost BoB. Our climate proxy and simulation results provide insights into past regional climate dynamics, suggesting reduced cloud cover, increased solar radiation, and air warming of the Himalaya and foreland areas and, as a result, glacier mass losses in response to weakened ISM. , Plain Language Summary Indian Summer Monsoon rainfall and Himalayan glacier/snow melts constitute the main water source for the densely populated Indian subcontinent. Better understanding of how future climate changes will affect the monsoon rainfall and Himalayan glaciers requires a long climate record. In this study, we create a 13,000‐year‐long climate record that allows us to better understand the response of Indian Summer Monsoon rainfall and Himalayan glaciers to past climate changes. The focus of our study is the time window between 9,000 and 22,000 years ago, an episode where the global climate experienced large and rapid changes. Our sediment record from the northern Bay of Bengal and climate change simulation indicate that during episodes of weak monsoon, the melting of the Himalayan glaciers increases substantially significantly. This is because the weakening of the monsoon results in less cloud cover and, as a result, the surface receives more sunlight and causes glacier melting. , Key Points Core sediments from the northern Bay of Bengal are a viable archive to reconstruct past changes in monsoonal and Himalayan meltwater runoff Weak monsoon reduces cloud cover and leads to increased radiative flux over the Himalaya and foreland areas and causes glacier mass loss A spatially integrated record of monsoon and Himalayan climate provides insights into regional climate dynamics

On the low-frequency variability of wintertime Euro-Atlantic planetary wave-breaking - Messori, Gabriele; Davini, Paolo; Alvarez-Castro, M. Carmen; Pausata, Francesco S. R.; Yiou, Pascal; Caballero, Rodrigo (Climate Dynamics, 2019)

Northern Hemisphere Land Monsoon Precipitation Increased by the Green Sahara During Middle Holocene - Sun, Weiyi; Wang, Bin; Zhang, Qiong; Pausata, Francesco S. R.; Chen, Deliang; Lu, Guonian; Yan, Mi; Ning, Liang; Liu, Jian (Geophysical Research Letters, 2019)
Abstract Changes in land cover and dust emission may significantly influence the Northern Hemisphere land monsoon precipitation (NHLMP), but observations are too short to fully evaluate their impacts. The “Green Sahara” during the mid‐Holocene (6,000 years BP) provides an opportunity to unravel these mechanisms. Here we show that during the mid‐Holocene, most of the NHLMP changes revealed by proxy data are reproduced by the Earth System model results when the Saharan vegetation cover and dust reduction are taken into consideration. The simulated NHLMP significantly increases by 33.10% under the effect of the Green Sahara. The North African monsoon precipitation increases most significantly. Additionally, the Saharan vegetation (dust reduction under vegetated Sahara) alone remotely intensifies the Asian (North American) monsoon precipitation through large‐scale atmospheric circulation changes. These findings imply that future variations in land cover and dust emissions may appreciably influence the NHLMP. , Plain Language Summary Northern Hemisphere land monsoon precipitation (NHLMP) provides water resources for about two thirds of the world's population, which is vital for infrastructure planning, disaster mitigation, food security, and economic development. Changes in land cover and dust emissions may significantly influence the NHLMP, but observations are too short to understand the mechanisms. The Sahara Desert was once covered by vegetation and dust emission was substantially reduced during the mid‐Holocene (6,000 years BP), which provides an opportunity to test the models' capability and unravel these mechanisms. Here we use an Earth System model and find that when the Saharan vegetation and dust reduction are taken into consideration, the simulated annual mean precipitation over most of the NHLM regions shows a closer agreement with proxy records. The sensitivity experiments show that the North African monsoon precipitation increases most significantly under the regional effects of “Green Sahara.” The Saharan vegetation (dust reduction under vegetated Sahara) alone also remotely increases the Asian (North American) monsoon precipitation through large‐scale atmospheric circulation changes. The knowledge gained from this study is critical for improved understanding of the potential impacts of the land cover and dust changes on the projected future monsoon change. , Key Points The first study of the impact of Saharan vegetation and dust reduction on the NHLMP Comparison with proxy records shows the effect of the Green Sahara improves the simulated NHLMP The Saharan vegetation and dust reduction significantly increase the NHLMP by 33.10%

Hydroclimate in the Pamirs Was Driven by Changes in Precipitation‐Evaporation Seasonality Since the Last Glacial Period - Aichner, Bernhard; Makhmudov, Zafar; Rajabov, Ilhomjon; Zhang, Qiong; Pausata, Francesco S. R.; Werner, Martin; Heinecke, Liv; Kuessner, Marie L.; Feakins, Sarah J.; Sachse, Dirk; Mischke, Steffen (Geophysical Research Letters, 2019)
Abstract The Central Asian Pamir Mountains (Pamirs) are a high‐altitude region sensitive to climatic change, with only few paleoclimatic records available. To examine the glacial‐interglacial hydrological changes in the region, we analyzed the geochemical parameters of a 31‐kyr record from Lake Karakul and performed a set of experiments with climate models to interpret the results. δD values of terrestrial biomarkers showed insolation‐driven trends reflecting major shifts of water vapor sources. For aquatic biomarkers, positive δD shifts driven by changes in precipitation seasonality were observed at ca. 31–30, 28–26, and 17–14 kyr BP. Multiproxy paleoecological data and modelling results suggest that increased water availability, induced by decreased summer evaporation, triggered higher lake levels during those episodes, possibly synchronous to northern hemispheric rapid climate events. We conclude that seasonal changes in precipitation‐evaporation balance significantly influenced the hydrological state of a large waterbody such as Lake Karakul, while annual precipitation amount and inflows remained fairly constant. , Plain Language Summary Lakes in arid Central Asia are particularly susceptible to the rise and fall of lake levels as a consequence of climatic changes. To evaluate drivers behind this phenomenon, we developed a record of humidity and lake levels throughout the last 31,000 years from a high‐altitude lake in the Pamir Mountains. Herefore, we combined hydrological and ecological reconstructions with climate model experiments. Results show that neither the enhanced inflow by melting glaciers nor the significantly increased precipitation amount was responsible for higher lake levels during the studied interval. Instead, reduced summer evaporation during cold episodes was the major trigger for lake transgressions. These fluctuations were driven by changes in radiative forcing (i.e., insolation and hence temperature change) as a consequence of changes in the Earth's orbit around the Sun. As such, our results suggest that a significant impact on lake levels in arid regions is also to be expected by the current anthropogenically driven global warming. , Key Points Proxies for hydroclimate and catchment ecology show insolation‐driven trends, with higher δD values during the LGM similar to outputs from climate models Reduced summer evaporation during cold episodes increased water availability Increased summer moisture caused higher lake levels at 31–30, 28–26, and 17–14 kyr BP coinciding with northern hemispheric rapid climate events